Faktor-Faktor yang Mempengaruhi Minat Generasi Muda Bekerja Pada Perusahaan Perkebunan - Era Susanti; Mirdha Fahlevi (Universitas Teuku Umar, 2021)
Abstract This study aims to explain the factors” that influence the interest of the younger generation to work in plantation companies. The population of this study is the entire young generation ranging from the age of 16-35 years. The sample in this study amounted to 172 respondents consisting of the younger generation with an age range of 16-35 years. The research shows that partially the independent variable, namely attitude (X1) has a positive and significant effect on the Variable Intention (Y) of the younger generation to work in plantation companies which is seen from the t- count value of 2.220 and a significant value of 0.028. Then continued with the subjective norm variable (X2) which has a positive and significant effect on the intention variable (Y) of the younger generation to work in plantation companies, which is seen from the t-count value of 2.068 and a significant value of 0.040. Behavioral control variable (X3) has a positive and significant effect on the intention variable (Y) of the younger generation to work in plantation companies, which can be seen from the